Children and Television: Using TV Sensibly - Murray, John P.; Lonnborg, Barbara (My University, 2004)
This publication is about managing how much time children spend watching TV and the affects of too much tmie watching TV.
L790_2004-12
Keywords: L790; Home and Family; Health and Safety; L